LncRNA NEAT1 Potentiates SREBP2 Activity to Promote Inflammatory Macrophage Activation and Limit Hantaan Virus Propagation - Yang, Yongheng; Li, Mengyun; Ma, Yongtao; Ye, Wei; Si, Yue; Zheng, Xuyang; Liu, He; Cheng, Linfeng; Zhang, Liang; Zhang, Hui; Zhang, Xijing; Lei, Yingfeng; et al. (Frontiers in Microbiology, 2022)
As the prototype of globally zoonotic hantavirus, Hantaan virus (HTNV) prevailed in Asia is the leading causative agent for severe hemorrhagic fever with renal syndrome (HFRS) with profound morbidity and mortality. Macrophages are the crucial components of host innate immune system which serve as the first line against HTNV infection. Previous studies indicated that the viral replication efficiency in macrophages determined hantavirus pathogenicity, while it remains enigmatic which factor manipulates macrophage activation pattern and the virus-host interaction process. Here, we performed transcriptomic analysis of HTNV-infected mouse bone marrow-derived macrophages, and identified the long non-coding RNA (lncRNA) nuclear enriched abundant transcript 1 (NEAT1), especially the isoform NEAT1-2, as one of the differentially expressed lncRNAs at the early phase. Based on the co-culture system, we revealed that silencing NEAT1-2 would hinder inflammatory macrophage activation and facilitate HTNV propagation, while enhancement of NEAT1-2 transcription could effectively restrain viral replication. Furthermore, sterol response element binding factor-2 (SREBP2), controlling the cholesterol metabolism process, was found to motivate macrophages by promoting multiple inflammatory cytokine production upon HTNV infection. NEAT1-2 could potentiate SREBP2 activity by upregulating Srebf1 expression and interacting with SREBP2, thus motivating inflammatory macrophages and limiting HTNV propagation. More importantly, we demonstrated that the NEAT1-2 expression level of patient monocytes was negatively correlated with viral load and HFRS disease progression. Our results identified a function and mechanism of action for the lncRNA NEAT1 in heightening SREBP2-medicated macrophage activation to restrain hantaviral propagation, and revealed its association with disease severity of HFRS.